Exploring Social Media Usage and Self-Image Congruity as Predictors of Online Conspicuous Consumption - Yunus , Asma; Bajwa , Ruqia Safdar; Mushtaq , Shahzad Khaver; Hussain , Malik Mureed (Pakistan Journal of Humanities and Social Sciences, 2023)
In the digital era, social media platforms play a vital role in shaping the self-image and consumption behaviors of individuals, making it essential to investigate the relationships between these variables. This study seeks to determine how Social Media Usage (SMU) and Self-Image Congruity (SIC) influence Online Conspicuous Consumption (OCC) among young adults. Using a cross-sectional survey methodology, a purposive sample of 262 individuals was recruited. The questionnaire contained four sections: Demographic information, SMU, SIC, and OCC questionnaires. To analyze the data, descriptive and inferential statistics were employed. Findings revealed a significant impact of social media usage and self-image congruity on online conspicuous consumption. The findings of this research contribute to the growing body of knowledge on the psychological and behavioral effects of social media and have significant implications for a wide range of stakeholders, such as individuals, marketers, legislators, and academics. Despite its limitations, this study provides the groundwork for future research into the complex interaction between SMU, SIC, and OCC in diverse cultural and geographic contexts. The findings can be used to inform marketing strategies, policy formulation, and ethical use of social media in the digital age, thereby enhancing individual and societal well-being.